2021
DOI: 10.1249/mss.0000000000002602
|View full text |Cite
|
Sign up to set email alerts
|

Factors Protecting against a Decline in Physical Activity during the COVID-19 Pandemic

Abstract: PurposeThe spread of COVID-19 and the associated stay-at-home orders and shutdowns of gyms and fitness centers have drastically influenced health behaviors leading to widespread reductions in physical activity (PA). The recent Call to Action from the American College of Sports Medicine has promoted “innovative strategies to promote PA during the COVID-19 pandemic.” We aimed to identify individual-level factors that protected against declines in PA levels amid the COVID-19 restrictions.MethodsWe used the Pennin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 40 publications
6
66
1
Order By: Relevance
“…Our main result of decreases in PA aligns with available data collected in individual countries (e.g., [16,17,19,20]). The same applies to more pronounced reductions in previously active individuals (e.g., [16,17,20]). In contrast, findings are less consistent with regard to sex and age.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our main result of decreases in PA aligns with available data collected in individual countries (e.g., [16,17,19,20]). The same applies to more pronounced reductions in previously active individuals (e.g., [16,17,20]). In contrast, findings are less consistent with regard to sex and age.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, findings are less consistent with regard to sex and age. Notwithstanding, interestingly, the reported magnitude of PA reductions here (41% to 42%) and guideline compliance declines (18.5%) was larger than reported from other surveys [16][17][18][19][20].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The total of 39 included manuscripts yielded a total of 118,022 participants with a range of job types. Twelve studies especially examined office workers [23,46,[50][51][52][53][54][55][56][57][58][59], and 11 studies [22,23,42,[44][45][46]52,[60][61][62][63] examined WFH or remote working.…”
Section: Main Characteristics Of the Studiesmentioning
confidence: 99%
“…For example, recent work studying youth long-distance runners found that COVID-19 social distancing restrictions impacted training habits (Bazett-Jones et al, 2020 ). Furthermore, recent studies have illustrated that physical activity levels during the COVID-19 global pandemic have decreased (Castañeda-Babarro et al, 2020 ; Gallè et al, 2020 ; Eek et al, 2021 ; Fearnbach et al, 2021 ; Puccinelli et al, 2021 ; Wilke et al, 2021 ). Self-reported moderate physical activity levels have been reported to decrease by 41%, while Eek and colleagues depicted that more than 65% of the participants reported changes in their physical activity (Eek et al, 2021 ; Wilke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%